(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2025)
This article reviews three categories that allow us to think about ways of connecting with the past when direct experience is not available: postmemory, borrowed memory, and affirmative memory. Based on their definitions, contexts, and critiques, their scope and limitations are examined in order to understand the ways in which certain communities, particularly in the context of student mobilizations, redefine and activate references to the past, assuming and claiming themselves as heirs. From a conception of memory as a social, political, and performative process, the article reflects on unconventional ways of remembering that do not necessarily fit into familiar or exclusively traumatic frameworks. In doing so, it proposes a preliminary framework for analyzing the articulation between memory and collective action in contemporary experiences.